Structural Reforms and Productivity Growth in Developing Countries : Intra- or Inter-Reallocation Channel? - Konté, Maty (World Bank, Washington, DC, 2021)
This paper investigates the effects of financial sector, product market, and trade reforms on labor productivity growth and its two components—the intra-sectoral (within) and inter-sectoral (between) components—in a sample of developing countries over 1975–2005. The paper finds that most of the past trade, product, and financial sector reforms have increased the growth rate of labor productivity. In particular, countries that are further away from the technology leader tend to benefit more from structural reforms than countries closer to the technology frontier. Looking at the subcomponents of labor productivity growth, the paper finds that structural reforms work mostly through the intra-allocative efficiency channel but not through the inter-allocative efficiency channel. The intra-sectoral component is the main driver of the impacts of reforms on labor productivity growth, with a contribution between 76 and 96 percent.